Asking the right questions?: a critical overview of longitudinal survey data on intimate partner violence and abuse among adults and young people in the UK - Skafida, Valeria (Journal of family violence, 2023)
Purpose: We undertake a critical analysis of UK longitudinal and repeated cross-sectional population surveys which ask about experiences of intimate partner violence and abuse (IPVA). Method: Seven relevant UK representative population-based surveys which ask about IPVA among adults and/or young people (16–17 years old) were identified. We critically engage with the questionnaires to analyse the strengths and limitations of existing UK data on IPVA. Results: Several limitations in UK surveys are identified. Many questions still show a bias, partly historical, towards collecting more data about physical abuse. Few surveys ask about financial abuse, abuse post-separation or through child contact, or through technologies, though improvements are under way. Surveys still seek to count incidents of abuse, instead of enquiring about the impact of abusive behaviours on victims. Ethnicity and other demographic variables are not always adequately captured (or accessible to data users), making it difficult to explore aspects of inequality. Potentially useful comparisons within the UK are difficult to undertake given the increasingly divergent questionnaires used in different UK nations. Conclusions: We discuss how future iterations of existing surveys or new surveys can improve with regards to how questions about IPVA are asked. Given that surveys across geographical contexts often suffer similar weaknesses, our findings will be relevant for IPVA survey methodology beyond the UK context.